Interleukin-17 and matrix metalloprotease-9 expression in the mycetoma granuloma. - Emmanuel Edwar Siddig; Ali Mahmoud Mohammed Edris; Sahar Mubarak Bakhiet; Wendy W J van de Sande; Ahmed Hassan Fahal (Public Library of Science (PLoS), 2019)
Mycetoma is a persistent, progressive granulomatous inflammatory disease caused either by fungi or by bacteria. Characteristic of this disease is that the causative agents organise themselves in macroscopic structures called grains. These grains are surrounded by a massive inflammatory reaction. The processes leading to this host tissue reaction and the immunophenotypic characteristics of the mycetoma granuloma are not known. Due to the massive immune reaction and the tissue remodeling involved, we hypothesised that the expression levels of interleukin-17 (IL-17) and matrix metalloprotease-9 (MMP-9) in the mycetoma granuloma formation were correlated to the severity of the disease and that this correlation was independent of the causative agent responsible for the granuloma reaction. To determine the expression of IL-17 and MMP-9 in mycetoma lesions, the present study was conducted at the Mycetoma Research Centre, Sudan. Surgical biopsies from 100 patients with confirmed mycetoma were obtained, and IL-17 and MMP-9 expression in the mycetoma granuloma were evaluated immunohistochemically. IL-17 was mainly expressed in Zones I and II, and far less in Zone III. MMP-9 was detected mainly in Zones II and III, and the least expression was in Zone I. MMP-9 was more highly expressed in Actinomadura pelletierii and Streptomyces somaliensis biopsies compared to Madurella mycetomatis biopsies. MMP-9 levels were directly proportional to the levels of IL-17 (p = 0.001). The only significant association between MMP9 and the patients' characteristics was the disease duration (p<0.001). There was an insignificant correlation between the IL-17 levels and the patients' demographic characteristics.